Notes on Time of Shedding of Antlers of Deer in Captivity - Acharjyo, L. N. (Indian Forester, 1971)
Some notes on the time of shedding of antlers of four kinds of deer observed at the Nandankanan Biological Park (Orissa) during the period from April, 1967 to September, 1970 have been reported and the observations of earlier reports have been cited.It is observed that the Sambars shed their antlers from April to July, the Spotted deer from November to February, the Hog deer (brought from outside the State) in December and the Barking deer in April and May.